DNA Methylation and Hydroxymethylation in Cervical Cancer: Diagnosis, Prognosis and Treatment - Zhu, Hongming; Zhu, He; Tian, Miao; Wang, Dongying; He, Jiaxing; Xu, Tianmin (Frontiers in Genetics, 2020)
Recent discoveries in our comprehension of the relationship between the epigenetics and tumor have led to new ideas and methods. Nowadays, worldwide scientists’ studies of the tumor are not only genetics but epigenetics as well. As more and more research about methylation in cervical cancer arises, it has been found that there is a specific correlation between the methylation of some genes and the progress of cervical cancer, which encompasses DNA methylation. Finding out the methylation modification of these genes will have clinical significance for early prevention, early diagnosis, recurrence monitoring, prognosis and treatment. In this review, we mainly focus on the significant impact on DNA aberrant methylation and DNA hydroxymethylation in cervical cancer and how to utilize these conclusions to guide the clinical application.